FAKTOR PENENTU KINERJA: PERAN INOVASI PROSES DAN INSTITUTIONAL SUPPORT PADA INDUSTRI MAKANAN DI SUMATERA BARAT - Ratni Prima Lita (Procuratio : Jurnal Ilmiah Manajemen, 2019)
West Sumatra became one of the tourist destinations that did through the improvement of the creative industry, especially in the food industry. This study aims to examine the effect of process innovation on the performance of the food industry, examine the effect of institutional support on the performance of the food industry, and examine the effect of institutional support on process innovation. A total of 60 respondents, namely the owners of the food industry in West Sumatra, were selected as samples in this study. The questionnaire was distributed to food industry owners and processed using the Structural Equational Modeling-PLS (SEM-PLS) method. The results of this study prove that process innovation and institutional support have a positive and significant effect on improving the performance of the food industry. Another finding is that institutional support also influences process innovation in the food industry in West Sumatra. These results indicate that there needs to be an increase in process innovation and also institutional support to improve performance in the food industry. Sumatera Barat menjadi salah satu destinasi wisata yang melalukan peningkatan industri kreatif terutama dalam industri makanan. Penelitian ini bertujuan untuk menguji pengaruh inovasi proses terhadap kinerja industri makanan, menguji pengaruh institutional support terhadap kinerja industri makanan, dan menguji pengaruh institutional support terhadap inovasi proses. Sebanyak 60 responden yakni pemilik industri makanan di Sumatera Barat dipilih sebagai sampel pada penelitian ini. Kuesioner disebarkan kepada pemilik industri makanan dan diolah menggunakan metode Structural Equational Modelling-PLS (SEM-PLS). Hasil dari penelitian ini membuktikan bahwa inovasi proses dan institutional support berpengaruh positif dan signifikan terhadap peningkatan kinerja industri makanan. Temuan lainnya adalah institutional support juga mempengaruhi inovasi proses pada industri makanan di Sumatera Barat. Hasil ini mengindikasi bahwa perlu adanya peningkatan dalam inovasi proses dan juga institutional support dalam upaya meningkatkan kinerja pada industri makanan.